Phenotypic screening meets natural products in drug discovery. Issue 1 (2nd January 2017) - Futamura, Yushi; Yamamoto, Kai; Osada, Hiroyuki
Abstract: The Nobel Prize in Physiology or Medicine 2015 was awarded for discoveries related to the control of parasitic diseases using natural products of microbial and plant origin. In current drug discovery programs, synthesized compounds are widely used as a screening source; however, this award reminds us of the importance of natural products. Here, we introduce our phenotypic screening methods based on changes in cell morphology and discuss their effectiveness and impact for natural products in drug discovery.